Fitoplancton de las lagunas Barba, Fraijanes y San Joaquín, Costa Rica - Umaña Villalobos, Gerardo (Revista de Biología Tropical, 1988)
The phytoplankton was studied in three small lakes located at different altitudes and climates, San Joaquín (10 m), Fraijanes (1660 m) and Barba (2840 m). They are similar in area and basic morphology. A total of 132 different taxa were found. The number of taxa decreased at higher altitude: San Joaquín 71, Fraijanes 63 and Barba 31. Chlorophyta was the richest group in the three lakes. Substantial differences were detected in the phytoplankton composition among the lakes. The global similarity at the lowest taxonomic level separation was 41.7%; San Joaquín and Fraijanes are the most similar lakes with 17% Jaccard similarity.